Peran Guru Terhadap Kebersihan Mulut Dan Gigi Pada Anak Usia Dini Di RA Al Aziziyah Kota Bekasi - Rosmawati, Cut (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
Dental health in early childhood needs attention and counseling efforts in maintaining oral and dental hygiene. One way to treat dental health in early childhood at school is to brush their teeth properly and thoroughly will help children maintain good dental and oral hygiene . This study aims to find out how the influence of teachers on dental and oral hygiene of children at an early age at RA Al Aziziyah Jatiasih School, Bekasi City. Researchers used a descriptive qualitative research method. Namely by interview techniques, observation, and documentation, observation guides, documents and field notes. The research subjects were students of the RA Al Aziziyah Jatiasih School, Bekasi City. Based on research, the teacher's role in maintaining children's dental hygiene includes brushing their teeth together and using various media related to dental hygiene